Differences in Awareness of Disease Between Young-onset and Late-onset Dementia. (April 2019) - Baptista, Maria A.T.; Santos, Raquel L.; Kimura, Nathália; Marinho, Valeska; Simões, José P.; Laks, Jerson; Johannenssen, Aud; Barca, Maria L.; Engedal, Knut; Dourado, Marcia C.N.
Abstract : Introduction: Awareness of disease is the ability to acknowledge changes caused by deficits related to the disease process. We aimed to investigate whether there are differences in awareness of disease between young-onset dementia (YOD) and late-onset dementia (LOD) and examined how awareness interacts with cognitive and clinical variables. Materials and Methods: Using a cross-sectional design, 49 people with YOD and 83 with LOD and their caregivers were included. We assessed awareness of disease, cognition, functionality, stage of dementia, mood, neuropsychiatric symptoms, and caregivers' quality of life (QoL) and burden. Results: We found that people with YOD were more aware of the disease than people with LOD ( P <0.005). Multivariate linear regression revealed that higher impairment in functional level was associated with unawareness in both groups (YOD= P <0.001; LOD= P <0.001). In the YOD group, preserved awareness was related to worse self-reported QoL ( P <0.05), whereas, in LOD, deficits in awareness were related to caregivers' worst perceptions about people with dementia QoL ( P <0.001). Conclusions: The findings highlight the distinct nature of awareness between YOD and LOD. The YOD group had higher levels of disease awareness compared with the LOD group, even though the first group had a greater impairment in functionality.